Validation of the Thai version of the incontinence impact questionnaire (IIQ-7) and the urogenital distress inventory (UDI-6) - Weerasopone, Soarawee; Santingamkul, Apirak (Chulalongkorn Medical Journal, 2023)
Background : The incontinence impact questionnaire (IIQ-7) and the urogenital distress inventory (UDI-6) have been developed to assess the impact of urinary incontinence on quality of life. The measure has to be tested for validity and reliability in particular populations before being officially used. Objective : To validate the Thai versions of IIQ-7 and UDI-6 for use in Thai-speaking populations. Design : An observational study. Setting : Division of Urology, Department of Surgery, Faculty of Medicine, Chulalongkorn University, Bangkok, Thailand. Materials and Methods : The translation into Thai followed the standard procedure. Forty-six patients with urinary incontinence were recruited to the study. Participants completed the two questionnaires upon their enrollment and after 1 week. Results : In the reliability analysis of IIQ-7, the internal consistency was 0.905 and the intraclass correlation was 0.939; 95% CI was between 0.89 and 0.966. As for UDI-6, the internal consistency was 0.68 and the intraclass correlation was 0.76;95% CI was between 0.566 and 0.867 Conclusions : The Thai IIQ-7 and UDI-6 are reliable, valid and consistent instruments for assessing symptom severity and the impact on QOL in Thai patients with urinary incontinence.